EMIRS Observations of the Aphelion‐Season Mars Atmosphere. Issue 15 (9th August 2022) - Smith, Michael D.; Badri, Khalid; Atwood, Samuel A.; Edwards, Christopher S.; Christensen, Philip R.; Wolff, Michael J.; Bertrand, Tanguy; Forget, François; Al Tunaiji, Eman; Wolfe, Christopher; Smith, Nathan; Anwar, Saadat
Abstract: Thermal infrared spectra taken by the Emirates Mars Infrared Spectrometer (EMIRS) on‐board the Emirates Mars Mission (EMM) spacecraft are well suited for the retrieval of surface temperatures, the atmospheric temperature profile from the surface to ∼40 km, and the column abundance of dust aerosols, water ice clouds, and water vapor. A constrained linear inversion retrieval routine that includes multiple scattering has been developed and optimized for this purpose. Here, we present a brief overview of the retrieval algorithm and first atmospheric science results from observations taken by EMIRS over the first Earth year of EMM Science Phase operations. These retrievals show extensive water ice clouds, typical for the aphelion season of these observations, and the expected north polar summer maximum and subsequent equatorward transport of water vapor is well documented. An unusually strong and early regional dust storm and its associated thermal response were also observed. Plain Language Summary: Data returned from the Emirates Mars Infrared Spectrometer (EMIRS) have been used to characterize the atmosphere of Mars. These data allow estimates of atmospheric temperature as a function of height, the amount of dust and water ice clouds in the atmosphere, and the abundance of water vapor. In this work we describe the process for estimating these quantities and we give a brief overview of our first results. The results show that Mars was relatively cool, relatively cloudy, but with little dust. This was expected given the season on Mars that was observed. More surprising was the observation of a dust storm that occurred earlier in the Martian year than usual. Key Points: Thermal infrared spectra of Mars taken by the Emirates Mars Infrared Spectrometer have been used to characterize the atmospheric state These aphelion season observations show the expected relatively cool atmosphere with prominent water ice clouds and generally little dust The initiation and evolution of a regional dust storm that occurred unusually early in the season was observed